Realistic interatomic potential for MD simulations - Eremeichenkova, Yu.V.; Metlov, L.S.; Morozov, A.F. (Физика и техника высоких давлений, 2003)
The coefficients of interatomic potential of simple form Exp-6 for neon are obtained. Repulsive part is calculated ab-initio in the Hartree-Fock approximation using the basis of atomic orbitals orthogonalized exactly on different lattice sites. Attractive part is determined empirically using single fitting parameter. The potential obtained describes well the equation of state and elastic moduli of neon crystal in a wide range of interatomic distances and it is appropriate for molecular dynamic simulations of high- temperature properties and phenomena in crystals and liquids.